Uit mijn soldatentijd 1914-1918 - Francken, Fritz (Berchem : John Lamoen, 1959)
Bibliotheek Camille Huysmans
Dedicator: Francken, Fritz, dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: Francken, Fritz; Wereldoorlog 1